2005
DOI: 10.1021/ic051078p
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Structures and Homolysis of Some Alkylcobalt(III) Phthalocyanine Complexes

Abstract: The first crystallographic data for sigma-bonded alkylcobalt(III) phthalocyanine complexes are reported. A single-crystal X-ray structure of CH(3)CH(2)Co(III)Pc (Pc = dianion of phthalocyanine) reveals that the solid consists of centrosymmetric face-to-face dimers in which the CH(3)CH(2)Co(III)Pc units retain their square pyramidal geometry. The structure appears to be the first one reported for a five-coordinate RCo(III)(chelate) complex with an electron-deficient equatorial system. The Co-C bond in CH(3)CH(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 67 publications
2
8
0
Order By: Relevance
“…), which may leave the M–C bond susceptible to thermolysis. Indeed, Galezowski and Kubicki reported that the Co(III)Pc–Me analogue (the phthalocyanine analogue of cobalamin) had a BDE of 126 kJ/mol and could be effectively broken by thermolysis (80 °C) . Thus, for applications that allow for phototriggered bond cleavage but must at the same time be relatively thermally stable (100–300 °C), the axial Si–C bond in Si phthalocyanines can provide essential specific control.…”
Section: Results and Discussionmentioning
confidence: 99%
“…), which may leave the M–C bond susceptible to thermolysis. Indeed, Galezowski and Kubicki reported that the Co(III)Pc–Me analogue (the phthalocyanine analogue of cobalamin) had a BDE of 126 kJ/mol and could be effectively broken by thermolysis (80 °C) . Thus, for applications that allow for phototriggered bond cleavage but must at the same time be relatively thermally stable (100–300 °C), the axial Si–C bond in Si phthalocyanines can provide essential specific control.…”
Section: Results and Discussionmentioning
confidence: 99%
“…From the structures, the complexes exhibit an overall octahedral geometry with a Co−C bond length similar to other alkyl-Co(III) complexes. 16,25,27,28 In particular, the metrical data of 2-Me is comparable to that of MeCbl with a Co−C bond length of 1.987 (4) vs 1.99 for MeCbl and Co− N1 of 2.072 (3) vs 2.19 in MeCbl. 29 Notably, the axial Co−N1 bond of 2-Me is shorter than the Co−N py bond using the pyN 4 platform (2.018(2)), showing how the pyrazole arms impose a more rigid environment around the cobalt center in comparison to alkylamines.…”
Section: ■ Results and Discussionmentioning
confidence: 75%
“…In addition, three of the 2-R derivatives were characterized using X-ray crystallography (Figure ). From the structures, the complexes exhibit an overall octahedral geometry with a Co–C bond length similar to other alkyl-Co­(III) complexes. ,,, In particular, the metrical data of 2-Me is comparable to that of MeCbl with a Co–C bond length of 1.987 (4) vs 1.99 for MeCbl and Co–N1 of 2.072 (3) vs 2.19 in MeCbl . Notably, the axial Co–N1 bond of 2-Me is shorter than the Co–N py bond using the pyN 4 platform (2.018(2)), showing how the pyrazole arms impose a more rigid environment around the cobalt center in comparison to alkylamines.…”
Section: Resultsmentioning
confidence: 79%
“…From the structures, the complexes exhibit an overall octahedral geometry with a Co-C bond length similar to other alkyl-Co(III) complexes. 16,25,27,28 In particular, the metrical data of 2-Me is comparable to that of MeCbl with a Co-C bond length of 1.987 (4) vs 1.99 for MeCbl and Co-N1 of 2.072 (3) vs 2.19 in MeCbl. 29 Notably, the axial Co-N1 bond of 2-Me is shorter than the Co-Npy bond using the pyN4 Hydrogen ).…”
Section: Synthesis and Characterization Of 2-rmentioning
confidence: 66%